Review of PRGF-HIPC Financing, the Adequacy of the Reserve Account of the PRGF Trust, and Subsidization of Emergency Assistance. (Policy Papers; Policy Paper ;, 2005)
This paper focuses on immediate PRGF and HIPC financing issues and does not discuss projections of the demand for, and supply of, resources for financing PRGF operations over the medium term. The latter issue will need to be revisited in the light of discussions on proposals for further debt relief and the Fund's future financial role in low-income countries.